Correction to: Photobiomodulation Therapy and Cell Therapy Improved Parkinson’s Diseases by Neuroregeneration and Tremor Inhibition - Ahrabi, Behnaz; Tabatabaei Mirakabad, Fatemeh Sadat; Niknazar, Somayeh; Payvandi, Ali Asghar; Ahmady Roozbahany, Navid; Ahrabi, Mahnaz; Dordshaikh Torkamani, Shaysteh; Abbaszadeh, Hojjat Allah (Journal of Lasers in Medical Sciences, 2025)
In the article titled “ Photobiomodulation Therapy and Cell Therapy Improved Parkinson’s Diseases by Neuro-regeneration and Tremor Inhibition” published in J Lasers Med Sci 2022;13:e28 (doi: 10.34172/jlms.2022.28), there was an error in the Ethical approval section. The ethics approval code was incorrectly reported as: “ The Ethics Committee of Shahid Beheshti University of Medical Sciences (SBMU) has legal the procedures on this; take a look at (IR.SBMU.RETECH.REC.1400.007).” The correct ethics approval code is: IR.SBMU.REC.1400.007 The corrected sentence should read: “ The Ethics Committee of Shahid Beheshti University of Medical Sciences (SBMU) has legal the procedures on this; take a look at (IR.SBMU.REC.1400.007.” This correction has now been updated in both the PDF and HTML versions of the article.